THE INFLUENCE OF PRODUCT PLACEMENT BY VIRTUAL INFLUENCERS ON INSTAGRAM ON AUDIENCE ATTITUDE - Tiffany, Fransisca; Cokki , Cokki (International Journal of Application on Economics and Business, 2024)
This study aims to examine the influence of product placement on the Instagram account of a virtual influencer (@allysagladys) on audience attitudes. The research sample consists of 308 students from Tarumanagara University in West Jakarta. The method employed for data collection in this study is convenience sampling, where questionnaires were distributed directly to the respondents. The results indicate that product placement on the virtual influencer's account can influence the formation of audience attitudes. Furthermore, the study suggests that companies should enhance their social media promotion through collaborations with influencers to shape and maintain audience attitudes toward their products.